« Pour le remède des âmes » : la chapelle du cimetière de l’hôpital Saint-Jacques de Cuiseaux et son décor peint - Denise Borlée (In Situ)
The Saint Jacques chapel in the cemetery of the poor people’s hospital at Cuiseaux (Saône-et-Loire) was founded 1406 by Jaquemet Turetel and his wife for the cure of his soul and those of his successors. The interior of the building, small and very simple, is decorated with beautiful murals, which are on the eastern wall composition organized around the central window. On both sides, and back to the north side, took a range of saints housed in false niches opened to the richly structured canopies. This well-preserved painted cycle, designed in keeping with the architectural framework, was also based on the integration of sculptural elements. Thus, the eastern window participates, by the light which it provides, in the painted on the embrasure Annunciation. Above, it is a wooden crucifix which completed the Crucifixion whereas the Resurrection of the Christ in high relief decorates the front of altar. On the same principle, a real statue of Jacques le Majeur, surmounted by a painted canopy in greyness and formerly polychromatic, takes part in the hagiographic procession. With the founders of the chapel represented to its feet, the superiority of the patron saint on the other saints only painted is clear. Modest Saint Jacques chapel, for the decoration of which some rich citizens of Cuiseaux seem to have joined, so offers a beautiful illustration of a close link between the arts at the beginning of the XVth century.